Population Pharmacokinetics of Sunitinib and its Active Metabolite SU012662 in Pediatric Patients with Gastrointestinal Stromal Tumors or Other Solid Tumors - Wang, Erjian (Eur J Drug Metab Pharmacokinet, 2021)
BACKGROUND AND OBJECTIVE: Population pharmacokinetic analysis explored the pharmacokinetics of sunitinib and its primary active metabolite, SU012662, in children and evaluated the sunitinib dose(s) that produce comparable plasma exposures to adults receiving the approved daily dose. METHODS: Data were from 65 children with gastrointestinal stromal tumors (GIST) or solid tumors. Pharmacokinetic models of sunitinib and SU012662 were developed using a systematic multi-step approach employing nonlinear mixed-effects modeling. The effect of predefined covariates on pharmacokinetic parameters was assessed. Final models were validated using visual predictive check and statistical techniques. RESULTS: The final dataset comprised 439 sunitinib and 417 SU012662 post-baseline plasma observations. Base models were characterized by two-compartment models with first-order absorption and lag time. Body surface area (BSA) was the only covariate that affected (P < 0.001) pharmacokinetic parameters for sunitinib and SU012662 and was incorporated into the final models. Bootstrap results indicated that the final models represented the final dataset adequately. Based on the final models, a sunitinib dose of ~ 20mg/m(2)/day in children with GIST aged 6–17 years would be expected to lead to similar total plasma exposures of sunitinib and SU012661 as a dose of 50 mg/day in an adult with GIST on schedule 4/2. CONCLUSIONS: In children with GIST or solid tumors receiving sunitinib, population pharmacokinetic analysis identified BSA as the only covariate that affected pharmacokinetic parameters and predicted a dose of ~ 20 mg/m(2)/day as achieving equivalent exposure to 50 mg/day in adults with GIST on schedule 4/2. TRIAL REGISTRATION: ClinicalTrials.gov identifiers (date registered): NCT01396148 (July 2011); NCT01462695 (October 2011); NCT00387920 (October 2006). SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13318-021-00671-7.